Pengalaman Keluarga dalam Melaksanakan Manajemen Diet Stroke Lansia - Suryawan, Ida Bagus Putu Rai; Suyasa, I Gede Putu Darma; Nuryanto, I Kadek; Wulandari, Sarah K (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to explore family experiences in implementing stroke diet management for older people in the Seririt Community Health Center working area. The method used is a qualitative method with a phenomenological approach. The results of the research show that there are four family experiences in implementing elderly stroke diet management in the Seririt Community Health Center working area, namely support for elderly stroke diet families in providing low-salt food and controlling the elderly's diet, post-stroke malnutrition related to nutritional management in elderly stroke sufferers for improving the nutritional status and improving the patient's metabolic quality, a healthy diet is one of the keys to successful stroke treatment which requires daily support from a healthy diet and nutritional counseling. In conclusion, there are four main themes: family support for elderly stroke diets, post-stroke malnutrition, healthy eating patterns, and nutritional counseling. Keywords: Family, Elderly, Diet Management of Stroke